The local theory of elastoplastic deformation processes and the stability beyond elastic limits of thin-walled structures subjected to complex loading - Bich, Dao Huy (Vietnam Journal of Mechanics, 1992)
The paper is concerned with the complete constitutive relations of elasto-plastic deformation process theory. Using this theory the stability beyond elastic limits of thin-walled structures subjected to complex loading is analyzed. The proposed method of loading parameter is a combination of numerical and analytical solutions. Calculations have been carried out for rectangular plates and cylindrical shells in order to compare this method and its results with other theoretical and experimental works.